Optimizing The Use of Microsoft Powerpoint to Improve Teacher Competence In Learning at SDN 1 Sempusari Jember - Siswanto, Edhi; Juhanda, Juhanda (Journal Of Humanities Community Empowerment, 2024)
In carrying out the task of selecting learning media, teachers must be able to determine the right type of media so that learning objectives are achieved effectively. Several factors that need to be considered in selecting learning media include: learning objectives, materials to be taught, student characteristics, appropriate types of media, the environment where students learn, and the availability of resources. Mastery of Information Technology in education is very necessary in accordance with the times, because teachers' ability to master information technology will affect the teaching and learning process for both teachers and students. However, there are still various factors that cause low mastery of information technology among teachers. Some teachers think that using learning media such as PowerPoint actually complicates their work. The target results of this community service activity are to improve the ability of elementary school teachers to present interesting presentations using Microsoft PowerPoint media. Participants consisting of elementary school teachers in the SDN 1 Sempusari Jember environment are expected to have additional insight and skills around Microsoft Power Point. The results of this activity show an increase in teachers' understanding and skills in using Microsoft PowerPoint. Through lecture methods, discussions, and question and answer sessions, participants are actively involved and are able to overcome various challenges faced in using this media. Overall, this activity has succeeded in improving teacher competence in utilizing technology to support the learning process